Dynamic behavior of flow around rows of square cylinders kept in staggered arrangement. Issue 136 (January 2015) - Chatterjee, Dipankar; Biswas, Gautam
Abstract: A two-dimensional numerical study is carried out to understand the vortex dynamics behind two rows of square cylinders arranged in a staggered fashion in an unbounded medium and at low Reynolds number ( Re =100). A uniform cross flow of an incompressible fluid is considered. The transverse spacing between the cylinders is varied ( S/d =1, 2, 3 and 5; with S and d are the transverse spacing and cylinder size) while the streamwise gap is fixed at L/d =1 ( L being the streamwise gap). Computations are performed by a finite volume based CFD solver using PISO algorithm. An unsteady two-dimensional laminar model is used for all the computations. Effect of transverse spacing on flow characteristics and global fluid dynamic parameters are discussed. Furthermore, the establishment of the low-dimensional chaotic nature of the flow is predicted for relatively small transverse spacing of the cylinders. The transition to chaos is manifested through a quasi-periodic route. The quasi-periodic route to chaos is established through different characterization tools, such as the spectra, autocorrelation function, time-delay reconstruction and the Poincare section. The chaotic behavior of the flow system is quantified through the calculation of the Lyapunov exponent and fractal dimension.